2009
DOI: 10.1007/s00213-009-1583-7
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation effect of combination therapy of aripiprazole and antidepressants on forced swimming test in mice

Abstract: The augmentation effects of aripiprazole, in the present study, are in agreement with clinical evidence suggesting that aripiprazole may enhance the efficacy of therapeutic effect of SSRIs and SNRIs but not of NRI. These results suggest that augmentation effect of aripiprazole only appears when 5-HT system is activated and might implicate complex regulation between dopamine and 5-HT(1A) and 5-HT(2A) receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 47 publications
3
34
1
Order By: Relevance
“…As a result, it has been proposed that the learned helplessness paradigm may be a model for evaluating antipsychotic-induced dysphoria but not for evaluating the antidepressant effects in antipsychotics. Another study (Bourin et al, 2009) showed that a single treatment with aripiprazole was not effective in reducing immobility in the forced swimming test, although coadministration of serotonin reuptake inhibitor (SSRI) with aripiprazole was found to be effective. Therefore, in this study, rather than using the above paradigms, we tried to use olfactory bulbectomy as another useful animal model for exploring antidepressant-like effects and found that lurasidone demonstrated similar effects like an antidepressant imipramine.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it has been proposed that the learned helplessness paradigm may be a model for evaluating antipsychotic-induced dysphoria but not for evaluating the antidepressant effects in antipsychotics. Another study (Bourin et al, 2009) showed that a single treatment with aripiprazole was not effective in reducing immobility in the forced swimming test, although coadministration of serotonin reuptake inhibitor (SSRI) with aripiprazole was found to be effective. Therefore, in this study, rather than using the above paradigms, we tried to use olfactory bulbectomy as another useful animal model for exploring antidepressant-like effects and found that lurasidone demonstrated similar effects like an antidepressant imipramine.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a single dose did not reduce immobility time in rats, however chronic administration of 7 and 14 days was successful in reducing this period. In another study in which aripiprazole was administered with other antidepressant medications, it was found to enhance the efficacy of other drugs in the forced swimming test 30 . However in another study in which rats were evaluated by the tail suspension test, aripiprazole monotherapy did not change the immobility time.…”
Section: Discussionmentioning
confidence: 98%
“…In experimental studies with different depression models, aripiprazole has been found to have antidepressant effects in rats 29,30 . Burada et al found that 6 mg/kg aripiprazole treatment decreased immobility time in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some preclinical reports indicates that agonist to ER increase dopamine and DOPAC (dopamine metabolite) levels in the hippocampus and the frontal cortex (Lubbers et al, 2010), areas involved in the effect of several antidepressant drugs. In fact, bupropion, a catecholamine enhancer, produces antidepressant-like actions in preclinical models (Reneric & Lucki, 1998;Dhir & Kulkarni, 2008;Bourin et al, 2009). …”
Section: Evidence Of Estrogens Interactions With the Dopaminergic Systemmentioning
confidence: 99%